Acipenser baerii Brandt 1869 ... - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Doadrio, Ignacio (Zenodo, 2020)
Acipenser baerii Brandt, 1869 – Non-native (Fig. 14) Acipenser baerii Brandt [J. F.] 1869: 115; Type locality: Ob and Lena river systems, Siberia, Russia. Syntypes: whereabouts unknown. Acipenser Nikolskii stenorrhynchus [A. M.] 1896: 400; Type locality: Large rivers of Siberia flowing to the Arctic. Syntypes: ZIN 10641 (2), 10885 (1), 10888 (1). ZISP 10641 also type of variety baicalensis. Acipenser stenorrhynchus var. baicalensis Nikolskii [A. M.] 1896: 401; Type locality: Lake Baikal, Siberia, Russia. Syntypes: MLSU 1631 (1), ZIN 10641 (2). Acipenser baeri hatys Dryagin [P. A.] 1948: 532; Type locality: From Lena to Kolyma rivers, Sakha-Yakutia, northeastern Russia. Syntypes: (27). Common name: Pr: Tas mahi baeri, En: Siberian sturgeon. Diagnosis: Extended snouts, four barbels in front of the mouth, the back is light grey to dark-brown colored, the belly color varies from white to clear yellow. Five rows of scutes, Small star-like scutes between the main ones. Clearly slit inferior lips. Meristic ... : Published as part of Jouladeh-Roudbar, Arash, Ghanavi, Hamid Reza & Doadrio, Ignacio, 2020, Fig. 4 in Fig. 4 in Fig. 3 in Fig. 21. Sesarmops mora n in Paralbunea dayriti, pp. 1-303 in Zoological Studies 59 (21) on page 13, DOI: 10.6620/ZS.2020.59-21, http://zenodo.org/record/12822787 ...